Paleosols in the Teotihuacan valley, Mexico: evidence for paleoenvironment and human impact - Emily McClung de Tapia; Elizabeth Solleiro-Rebolledo; Jorge Gama-Castro; José Luis Villalpando; Sergey Sedov (Revista Mexicana de Ciencias Geológicas)
The Teotihuacan valley, located in the northeastern sector of the basin of Mexico, was settled by approximately 1,100 BC. The first and largest prehistoric city in the Americas developed here in AD 350–550, reaching a population of around 125,000. The demise of the Teotihuacan state is now generally believed to have culminated between AD 600–650. Causes are attributed to global climate change, environmental degradation, economic and/or political upheaval, but no direct evidence has ever been presented to support these hypotheses. The study of paleosols contributes to the understanding of the environmental conditions that prevailed in the Teotihuacan region in order to better comprehend their potential relationship to cultural and economic events in the prehistoric past. The distribution of soils in the region is directly associated with relief. Profiles at Cerro Gordo (3,050 m a.s.l.) and Cerro Patlachique (2,700 m a.s.l.) are associated with forest conditions, where paleosols are characterized by polygenetic profiles with varying degrees of development. The older soils are represented by Luvisols. Soils in lower positions (Cerro Colorado, 2,390 m a.s.l.) are stratified and poorly developed, with evidence of colluvial deposition and erosion. Soils with fluvic properties in the alluvial plain (2,250–2,350 m a.s.l.) are also poorly developed and greatly influenced by erosive processes and intensive accumulation. Those corresponding to the Teotihuacan periods (2,000–1,350 yr BP) show multiple indicators of human impact. Micromorphological evidence indicates intensive agricultural activities (deforestation, burning, compaction, and erosion). The presence of carbonates in underlying strata is related to changes in humidity. Phytoliths identified from the same strata indicate alterations in vegetation through time that reflect variable conditions of temperature and humidity. The results clearly reflect environmental modification by human populations from the initial period of prehistoric settlement up to present. Furthermore, the evidence suggests that a major impact of the prehistoric city on the landscape resulted from unmanaged exploitation of forest resources that provoked intensive erosion and significant changes in the hydric conditions of the region.